(untitled) (AYUSHDHARA, 2021)
Regular periods are necessary to maintain good health of women. Any abnormality in Rituchakra leads to excessive and irregular uterine bleeding which is known as Asrigdara which can be correlated to Abnormal Uterine bleeding. In Ayurvedic text, many preparations are described to treat Asrigdara. Samshodhan therapy is mainstay in the management of Artava related disorders of which Basti is supreme to manage Asrigdara. In conventional science, Hormonal therapy is given but chances of recurrence of the disease are high. This study was planned to provide simple, safe, non- hormonal drug for the patients of Asrigdara. Total 40 patients fulfilling the inclusion criteria were selected randomly from Dept. of Stree roga and Prasuti tantra O.P.D.and I.P.D. The total effect of drug was evaluated on the basis of signs and symptoms after completion of therapy. Overall effect of therapy shows in group-I 6 (60%) patients were markedly improved, 11 (61.11%) were partially improved and 1 (5.6%) was not improved and group II- 6 (33.33%) patients were cured, 9 (50%) were markedly improved, 2 (11.1%) were partially improved, and 1 (5.6%) was unimproved. Thus, Basti Chikitsa manifested promising results for the management of Asrigdara, although hormonal pill manifested better cycle but for shorter duration.